Urgensi kolaborasi stakeholder dalam mewujudkan akuntansi lingkungan - Musa, Nur Khalisa M. (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: This study aims to reveal the implementation of environmental accounting at PT Huadi Nickel-Alloy Indonesia, analyze stakeholder collaboration in the implementation of environmental accounting at PT Huadi Nickel-Alloy Indonesia, and explore the urgency of stakeholder collaboration in the implementation of environmental accounting at PT Huadi Nickel-Alloy Indonesia. Methods: This type of research is classified as qualitative research with a case study approach. The data source for this study is primary data obtained through observation and interviews with internal and external stakeholders of PT Huadi Nickel-Alloy Indonesia. In addition, this study also uses secondary data obtained from the company profile, the company's AMDAL document, the company's RKL-RPL document, the company's environmental permit document and related articles. The data analysis technique in this study was carried out through three stages, namely: data reduction, data presentation and drawing conclusions. Findings: The results of this study found that PT HNAI in implementing its environmental accounting does not yet have a special environmental cost report. The environmental costs incurred are only recorded in the environmental cost account in the company's financial statements. The financial statements of PT HNAI cannot be accessed by researchers. In addition, the effects of environmental costs incurred by PT HNAI have not been able to significantly minimize the environmental impacts felt by residents. Conclusion: Stakeholder collaboration in the implementation of environmental accounting at PT HNAI has not fully met the requirements for collaboration. Because ideally, of the 8 components used in this study as a measure of the success of a collaboration, PT HNAI stakeholder collaboration can only meet 3 components of collaboration. PT HNAI and its external stakeholders have different interests. However, even so, both PT HNAI and its external stakeholders have the same needs for the sustainability of their environment. Therefore, it is very important to collaborate between stakeholders in the process of achieving common goals in terms of maintaining environmental sustainability as a source of livelihood for all creatures.